A Phosphatidyl Conjugated Telomerase-Dependent Telomere-Targeting Nucleoside Demonstrates Colorectal Cancer Direct Killing and Immune Signaling - Merve Yilmaz; Sibel Goksen; Ilgen Mender; Gunes Esendagli; Sefik Evren Erdener; Alessandra Ahmed; Ates Kutay Tenekeci; Larisa L. Birichevskaya; Sergei M. Gryaznov; Jerry W. Shay; Z. Gunnur Dikmen (Biomolecules)
Telomerase and telomeres are crucial in cancer cell immortalization, making them key targets for anticancer therapies. Currently, 6-thio-dG (THIO) combined with the anti-PD-1 inhibitor Cemiplimab is under phase II clinical investigation (NCT05208944) in NSCLC patients resistant to prior immunotherapies. This study presents the design, synthesis, and evaluation of novel bimodular conjugate molecules combining telomere-targeting nucleoside analogs and phosphatidyl diglyceride groups. Among them, dihexanoyl-phosphatidyl-THIO (diC6-THIO) showed high anticancer activity with sub-µM EC50 values in vitro across various cancer cell lines. In mouse colorectal cancer models, diC6-THIO demonstrated strong anticancer effects alone and in combination with PD1/PD-L1 inhibitors. Administration of this compound resulted in the efficient formation of Telomere dysfunction Induced Foci (TIFs) in vitro, indicating an on-target, telomerase-mediated telomere-modifying mechanism of action for the molecule. Systemic treatment also activated CD4+ and CD8+ T cells while reducing regulatory T cells, indicating immune system enhancement. Notably, diC6-THIO exhibits an improved solubility profile while maintaining comparable anticancer properties, further supporting its potential as a promising therapeutic candidate. These findings highlight diC6-THIO as a promising telomere-targeting prodrug with dual effects on telomere modification and immune activation.